FOOD ADDITIVES, DIETARY AND BIOLOGICALLY ACTIVE ADDITIVES - Sultonova Husnidakhan Hasanjon kizi (American Journals, 2024)
The article considers the classification of secondary resources formed during the processing of plant material. It has been established that, from the point of view of valuable macronutrients, secondary resources formed during the processing and canning of fruits and vegetables, in the production of vegetable oils, products of the milling and grain industry, as well as during the processing of grapes are of the greatest interest. Currently, despite the large number of developed and implemented technologies, it has been concluded that developments providing complex processing of plant material to obtain food and biologically active additives are relevant.
Keywords: Secondary plant resources, food additives, biologically active food additives, food production.